Global and Thai Energy Crop for Biofuel: A Comprehensive Research Data Analysis - Borisoot Kanjanapon; Paphapote Tawan; Suksri Amnart; Wongwuttanasatian Tanakorn (E3S Web of Conferences)
Using fossil fuels for electricity generation has led to critical environmental and economic challenges. Hence, alternative energy resources are more appealing for addressing these challenges. Energy crops are one of the alternative energy sources, and as renewable feedstocks for biofuel production, they offer a promising solution to reduce reliance on fossil energy sources. The analysis aims to uncover global and Thailand specific research trends, advancements, and existing gaps. This analysis conducts a bibliometric analysis of scientific publications on energy crops for biofuel, using data from the Scopus database (1987–2024) and VOSviewer software. The findings reveal global research on energy crops has progressed through three phases: initial exploration (1987–2005), rapid growth (2006–2018), and a recent decline (2019–2024). Thailand’s research, starting in 2009 and growing after 2020, remains limited compared to global leaders like the United States. This underscores the urgent need for Thailand to align its research efforts with global advancements. Policy support is critical to bridging the gap between research and practical applications, enabling Thailand to unlock the full potential of energy crops. Future research for energy crops should prioritize integrating biohydrogen production and advancing carbon management, particularly through technologies like carbon sequestration and lifecycle assessments.